Using Massive Open Online Course (MOOC) on Pancasila Education Increasing Students’ Score - Sukriono, Didik; Sudirman, Sudirman (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This article analyzes the development of virtual learning capabilities through massive open online courses (MOOC) on Pancasila Education. The Pancasila Education course has only been delivered in traditionally managed classes by relying on face-to-face meetings. Therefore there needs to be a new approach in Pancasila education to deal with 21st century learning. This research was designed as a research and development education (R&D). Starts with developingthe MOOC Pancasila education platform and conducting tests on students. The research instrument used in this study was the learning outcomes (scores) of students taking Pancasila education courses. The data analysis used is the independent sample t test, which is a statistical test to find out the differences between two samples that are not interconnected. The result of the development is known that virtual learning through the MOOC platform can increasing students’ score. That are known from the average of virtual class score than traditional classes, but the level of equality is lower values than virtual classes. This average that not all students in one membership can receive virtual classes equally. The traditional and virtual classes of the Pancasila education has a significant difference